(untitled) - SYAIFULLOH, MUHAMMAD (Jurnal Ilmu Manajemen (JIM), 2013)
Indonesian health develop significantly in decades. This ispartly due to the modern lifestyle is not healthy, and followed by baddiet cause decreasement of people health. Quaker applies theinteractive marketing in order to ease consumer in searching QuakerOats’s information and to build and develop consumer purchaceintention. Limitation of this study is gymnasium member who care ofheart health and access the Quaker Oats website one time or more inage range 25-55 years old. The samples used as much as 80 people,using quota sampling technique. The research instrument that usedwas a questionnaire, and multiple linear regression analysis. Thisstudy shows the results, that there is a positive effect betweenhealthy lifestyle and interactive marketing towards purchase intentionQuaker Oats simultaneously. In partially healthy lifestyle nosignificant effect on purchase intention.Keywords: healthy lifestyle, interactive marketing, purchase intentionand quaker oats.